2009
DOI: 10.3748/wjg.15.2449
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and epidemiology of spondyloarthritides associated with inflammatory bowel disease

Abstract: Inflammation of axial and/or peripheral joints is one of the most frequent extra-intestinal manifestations complicating the clinical course and therapeutic approach in inflammatory bowel diseases (IBD). The frequency of these complications seems to be similar for both diseases, Crohn's disease and ulcerative colitis. Arthritis associated with IBD belongs to the category of spondyloarthropathies. Axial involvement ranges from isolated inflammatory back pain to ankylosing spondylitis, whereas peripheral arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 43 publications
(16 reference statements)
1
69
1
7
Order By: Relevance
“…Prevention of progressive structural damage, preservation/normalization of function, and social participation are key points in treating to target patients affected by SpA [18]. Data from literature showed that the prevalence of peripheral arthritis in IBD patients varies from 11% to 20% and AS prevalence ranged from 3% to 6% [12]. In this study we demonstrated that joint involvement has a prevalence of 18% in a large cohort of 1495 IBD patients evaluated in the same period while ESpA has a prevalence of 9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention of progressive structural damage, preservation/normalization of function, and social participation are key points in treating to target patients affected by SpA [18]. Data from literature showed that the prevalence of peripheral arthritis in IBD patients varies from 11% to 20% and AS prevalence ranged from 3% to 6% [12]. In this study we demonstrated that joint involvement has a prevalence of 18% in a large cohort of 1495 IBD patients evaluated in the same period while ESpA has a prevalence of 9%.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the joint involvement observed in IBD was usually classified mainly into two subsets: axial (including sacroileitis with or without spondylitis) and peripheral [10,11]. Evidence shows that the frequency of the joint involvement in IBD is affected by the criteria applied to define the clinical findings [12]. In particular, axial involvement is present in 2-16% of IBD patients and the prevalence of sacroileitis (asymptomatic and symptomatic) is 12-20%, ranging from 3.9% to 18.9% when HLA-B27 is associated [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral arthropathy (pauciarticular, asymmetrical and migratory) occurs in 10-20% of inflammatory bowel disease (IBD) patients and is characterized by a recurrent nature and a parallel course with CD (11)(12)(13). In contrast, axial arthropathy shows an independent course of CD and includes sacroiliitis, with a prevalence of 12-25%, and ankylosing spondylitis, with a prevalence of 2-16% in Crohn's patients (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic predisposition and environmental factors have been implicated in the pathogenesis of AS [1,2]. With new and very effective therapeutic approaches, such as biologics becoming available, it is imperative to recognize and treat AS as early as possible in order to prevent disability.…”
Section: Introductionmentioning
confidence: 99%